Implementation Of The Strategy Peer Lesson To Increase Learning Value Of Students Class Seventh In Tajwid Lesson In Middle School Of Sulamul Huda Ponorogo - Muhammad Mukhlas; Muh Toha Abdurrahman (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
The existence of learning was expected to change attitudes and behavior of a personin several aspects such knowledge, skills, even to the attitude of his personality. Learning with sincerity will bring good change so that the learning activity of students could increase rapidly. One of learning strategy in increasing student activity is peer lesson. The purpose of this study aimed: 1) to explain the increasing of learning activity by peer lesson in tajweed lesson in class VII in Sulamul Huda Siwalan. (2) To explain the increasing learning result of peer lesson strategy in tajweedl esson in class VII Sulamul Huda Siwalan. The type of research was Classroom Action Research (PTK) to improve the process and results the quality of learning. Researchers collected data in the form of questionnaires, observations, tests, and interviews. The results of this study indicated that: (1) The implementation of the strategy peer lesson could increase the learning activity of students in the first cycle, most of the students included in the high category reached 73.91% of the total students, then increased in the second cycle reached 86.96% of the total number of students. (2) The implementation of the strategy peer lesson could increase student learning result in the second cycle of students who were classified as complete in learning totaling 18 students or 78.26% of the total number of students, that compared to the first cycle has increased by 10 students or 43, 58% of the total number of students. Based on the research, the researcher expects for the teacher to apply the strategy peer lesson in the learning process to take place.